Application of lentil flour (lens culinaris) as a substitute for wheat flour in pastry doughs. - Cevallos Echeverría, Priscila; Parrales Bosada, Yuri Yuliana; Zamora Bravo, Mayra Alejandra (Ingeniería Química y Desarrollo, 2024)
Ecuador is a diverse country in products of all kinds and an essential part of its wealth are legumes, in the Ecuadorian mountain range the cultivation of legumes is done in a traditional way and they are of great importance for the inhabitants, but nowadays its use is  limited, it presents the problem that many of this legumes are not of interest to the population in the bakery industry, which is why this project has as a general objective to apply lentil flour as a substitute for wheat flour in pastry doughs.  Through this research it’s possible to determine that pastry doughs can not only be made with wheat flour, but also with a partial replacement with lentil flour, for this study an experimental methodology will be used in obtaining lentil flour and the formulation of pastry products, in addition, the qualitative method will be used through sensory analysis of products made from lentil flour that will be evaluated through preference tests and acceptance tests.
Keywords: lentil; substitution; heavy dough; light dough; cutting mass